Diseño y construcción de un prototipo generador de energía eléctrica con accionamiento mecánico por el tránsito de bovinos para energizar un dispositivo de distanciamiento de murciélagos (2021)
It is identified as a problem the finding of bats bites in cattle on farms in the department of La Guajira, generating an economic imbalance for farmers in the region; thus, it was designed and built a prototype single-phase power generator powered by cattle traffic, in order to scare away the bats from the stables and thus reduce the loss they are causing by the above mentioned; In this way, we studied and analyzed all the factors to be taken into account such as the weight of the cattle, the energy needed to generate, the dimensions of the prototype and the strategic point for its installation, we made calculations of its performance, thus achieving a self-sustainable machine that minimizes the expenditure of electricity to power an ultrasound device to scare away the bats from the stables.